Peran Penting Hukum Internasional Dalam Menjaga Keamanan Dunia Dalam Perdagangan Manusia di Kamboja Vietnam dan Thailand - Triadi, Irwan; Maharani, Aulia Cantika; Al Anshari, Muhammad Faqih; Purba, Diana Febri Nauli; Darsono, Leandra Aurelrio Putra (Media Hukum Indonesia (MHI), 2025)
Human trafficking poses a serious challenge in the modern world and requires serious attention from the international community. This journal discusses the role of international law in efforts to combat human trafficking through a review of literature studies. By analyzing various prior studies and related reports, this article investigates on how international legal developments seek to address this issue of human trafficking. Through a literature study, this article identifies the various international legal approaches that have been taken to address human trafficking as well as evaluates the effectiveness of measures as well as the challenges faced by the international community in combating human trafficking. The results of this literature review provide an understanding of the international legal landscape related to human trafficking, as well as identify areas where further efforts are needed. This article concludes the importance of interstate cooperation and effective implementation of laws in efforts to combat human trafficking effectively worldwide.